"Words are picked up along the way" – Swedish EFL teachers' conceptualizations of vocabulary knowledge and learning. Issue 4 (29th November 2022) - Bergström, Denise; Norberg, Cathrine; Nordlund, Marie
Abstract: Vocabulary is a core feature of language proficiency, requiring explicit attention in the language classroom. As teachers' conceptualizations influence their teaching, their understanding of vocabulary deserves closer attention. Yet, few teacher cognition studies focus on vocabulary, and even fewer on non-native teachers' conceptualizations of vocabulary. This paper presents an interview study with Swedish EFL teachers at secondary school level. Fourteen teachers were interviewed about their beliefs and practices in relation to vocabulary development in the classroom. The study shows that despite a general understanding of the importance of vocabulary in language learning among the teachers, vocabulary was not seen as a learning objective in its own right. Closely connected to this understanding, the teachers showed a great reliance on incidental vocabulary learning, where words were understood as "picked up along the way" while doing other things, such as reading and playing games. It was also found that although the teachers showed an awareness of the many aspects involved in word knowledge, they mentioned few methods to work with them. The study suggests a need for a more explicit focus on vocabulary instruction in the language learning classroom.